Efeitos da estimulação elétrica na arquitetura muscular do quadríceps femoral pós revascularização do miocárdio - Castagna, Letícia (2018)
Coronary artery bypass grafting (CABG) is a highly complex procedure that can trigger a series of postoperative muscle skeletal complications as a result of the association with the extracorporeal circulation, compromising the metabolism of peripheral tissue and resulting in decreased functional capacity (FC) and loss of muscle mass. Ultrasonography is a fundamental instrument for musculoskeletal evaluation. In order to restore physical and psychosocial function, it is recommended the use of cardiac rehabilitation programs (CRP), emphasizing a multidisciplinary approach, such as the inclusion of physicaltherapy. Therefore, among the physicaltherapy resources, there is functional electrical stimulation (FES). This study aims to investigate the effects of adding FES to CRP in post-CABG patients. It is a randomized double-blind clinicial trial involving 24 patients (59,5±9,44 years, 17 male) who were randomly assigned to a control group (CG; n=11) submited to FES Sham associated with CRP, and also an intervention group (IG; n=13) submitted to FES associated with CRP, during 12 weeks. The following outcomes were evaluated pre and post intervention: femoris quadriceps muscle thickness, femoris rectus cross-sectional area, vastus intermedius and femoris rectus echogenicity, pheriperal muscle strenght, muscular resistance, and submaximal functional capacity. In CG and IG there was significant increase in EMQ, femoris rectus cross-sectional area, pheriperal muscle strenght, limbs lower muscle endurance and quality of life and submaximal functional capacity of post-CABG patients. The quality of rectus femoris muscle increased significantly in IG compared with GC, while intermedius vastus muscle qualitative increased significantly in both groups. Low frequency FES combined with CRP reduced the the rectus femoris echointensity, which allows to infer that there was an increase in musculoskeletal quality compared to the patients who received FES sham. In this way, it is suggested the continuity of studies to elucidate the eficcacy of low frequency electrical stimulation implementation in cardiac rehabilitation patients